Experimental verification of the effect of the form (scaly or scaleless) of carp host (C. carpio L.) on the growth rate of micropopulations of Gyrodactylus katharineri Malmberg, 1964 (Monogenea) - Gelnar, M (Folia parasitologica, 1987)
It was demonstrated that the growth rate of Gyrodactylus katharineri micropopulations parasitizing the fry of Cyprinus carpio L. was effected by water temperature and by the form of the fish host (scaly or scaleless). At lower water temperature (12 degrees C) the number of parasites increased in both host forms approximately at the same intensity. In warmer water (18 degrees C), the parasites reproduced intensively only on the scaly form of fish, whereas no parasites were found on the scaleless form some days after infection.
Keywords: Cyprinidae; Trematoda; sladká voda; zvířata; teplota; Temperature; Fresh Water; Animals; Carps; kapři